Accumulating Knowledge Over Time Introduction to the Fourth FBR Review Issue - Cruz, Cristina; Brigham, Keith; Kammerlander, Nadine; Kotlar, Josip (SAGE Journals, 2022)
[No abstract available]
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 4 - Educación de calidad; ODS 9 - Industria, innovación e infraestructura